The effect of MHD on Marangoni boundary layer of hybrid nanofluid flow past a permeable stretching surface - Abdullah, Nur Nazirah; Mohamad Som, Ahmad Nazri; Md Arifin, Norihan; Ab Ghani, Aniza (Semarak Ilmu, 2022)
Numerous researchers studied on the properties of hybrid copper-alumina/water nanofluid in order to have better thermal efficiency that could be used in industrial applications. Therefore, the present study accentuates the effect of MHD on Marangoni boundary layer of hybrid copper-alumina/water nanofluid flow over a stretching surface. Furthermore, the governing boundary layer equations which is partial differential equations (PDEs) are transformed into a set of ordinary differential equations (ODEs) using similarity transformations. Then, these problems are solved numerically using shooting method through Maple software. It is shows that the rate of heat transfer decreases with the increase in magnetic parameter. The velocity and temperature profiles, as well as local Nusselt number are observed with the specific parameter namely, magnetic parameter, nanoparticles volume fraction and suction. By increasing the volume fraction for copper and magnetic parameter, the velocity profiles decrease while the temperature profiles increase.